PENGARUH PERSEPSI KINESTETIK TERHADAP KEMAMPUAN HANDSPRING ON VAULT ATLET PERSANI SULAWESI SELATAN - Ferawati, Ferawati (Jurnal Penjaskesrek, 2017)
The Gymnastic;s team of South Sulawesi has high pride but need to increase coaching in terms of breeding and improvement of exercise programs. This research is a type of correlational research with aim of knowing kinesthetic perception relation to handspring ability on Vaulting Table. The data  instruments were kinesthetic obstacle test and handspring Vaulting Table test on 30 samples of artistic gymnastics athlete. Data analysis technique with Pearson correlation analysis to describe the relationship of two variables derived from normal distributed data. The result of hypothesis test with correlation analysis obtained correlation coefficient value r 0.704 ** which shows strong and positive relationship level and probability value 0.000 (sig <α 0.05) means there is significant correlation between kinesthetic perception and handspring ability on Vaulting Table.